Alcohol and risk of Barrett’s esophagus: a pooled analysis from the international BEACON consortium - Thrift, Aaron P. (2014)
BACKGROUND: Results from studies examining the association between alcohol consumption and the risk of Barrett’s esophagus have been inconsistent. We assessed the risk of Barrett’s esophagus associated with total and beverage-specific alcohol consumption by pooling individual participant data from five case-control studies participating in the international Barrett’s and Esophageal Adenocarcinoma Consortium (BEACON). METHODS: For analysis there were 1282 population-based controls, 1418 controls with gastroesophageal reflux disease (GERD) and 1169 patients with Barrett’s esophagus (cases). We estimated study-specific odds ratios (OR) and 95% confidence intervals (95% CI) using multivariable logistic regression models adjusted for age, sex, body mass index (BMI), education, smoking status, and GERD symptoms. Summary risk estimates were obtained by random effects models. We also examined potential effect modification by sex, BMI, GERD symptoms and cigarette smoking. RESULTS: For comparisons with population-based controls, while there was a borderline statistically significant inverse association between any alcohol consumption and the risk of Barrett’s esophagus (any vs. none, summary OR=0.77, 95% CI 0.60–1.00), risk did not decrease in a dose-response manner (p(trend)=0.72). Among alcohol types, wine was associated with a moderately reduced risk of Barrett’s esophagus (any vs. none, OR=0.71, 95% CI 0.52–0.98); however, there was no consistent dose-response relationship (p(trend)=0.21). We found no association with alcohol consumption when cases were compared with GERD controls. Similar associations were observed across all strata of BMI, GERD symptoms and cigarette smoking. CONCLUSIONS: Consistent with findings for esophageal adenocarcinoma, we found no evidence that alcohol consumption increases the risk of Barrett’s esophagus.